2019
DOI: 10.1155/2019/3128231
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Olfactory Dysfunction, Frailty, and Mortality Is Mediated by Inflammation: Results from the InCHIANTI Study

Abstract: Background. Olfactory dysfunction might unveil the association between ageing and frailty, as it is associated with declining cognitive function, depression, reduced physical performance, reduced dietary intake, and mortality; all these conditions are characterized by increased levels of inflammatory parameters. The present study is aimed at evaluating the association between olfactory dysfunction, frailty, and mortality and whether such association might be mediated by inflammation. Methods. We analysed data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 34 publications
(38 reference statements)
5
54
0
Order By: Relevance
“…As such, gait speed may reflect overall health in a similar manner as the state of the olfactory system ( 40 ). Indeed, some previous findings suggest a significant overlap between frailty, inflammatory markers, and OD ( 41 , 42 ). Note, however, that gait speed was not associated with olfactory change in multi-adjusted models, again indicating significant overlap with comorbidities.…”
Section: Discussionmentioning
confidence: 95%
“…As such, gait speed may reflect overall health in a similar manner as the state of the olfactory system ( 40 ). Indeed, some previous findings suggest a significant overlap between frailty, inflammatory markers, and OD ( 41 , 42 ). Note, however, that gait speed was not associated with olfactory change in multi-adjusted models, again indicating significant overlap with comorbidities.…”
Section: Discussionmentioning
confidence: 95%
“…A decrease in basal cell proliferation with age can be explained by decreased expression of cyclin D, a transcription factor for cell proliferation, and decreased expression of growth factors such as epidermal growth factor, insulin-like growth factor-1, and neuropeptide Y signalling 16,17 The repeated damage of olfactory receptor neurons might also be associated with decreased proliferation of basal cells after excessive www.nature.com/scientificreports/ basal cell divisions 18 . In addition, pro-inflammatory cytokines from senescent cells may induce the suppression of basal cell proliferation and loss of olfactory receptor neurons as aging-related physiological changes 19,20 . Several previous studies have proposed possible mechanisms for association of CVD and its risk factors with olfactory dysfunction 12,[21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…Controlling for smoking or alcohol abuse did not attenuate the link between OI and mortality (Pinto et al, 2014;Devanand et al, 2015). Some authors also suggested that high levels of inflammatory markers (interleukin-6, C-reactive protein) could be associated with frailty, atherosclerosis and also with OI (Schubert et al, 2011;Henkin et al, 2013;Laudisio et al, 2019). However, adjusting for these variables did not attenuate the link between OI and mortality (Schubert et al, 2016).…”
Section: Reflection Of General Poor Healthmentioning
confidence: 98%